How Do Profitability and ISO 14001 Certification Impact on Sustainability Reporting? - Handayani, Susi; Triani, Ni Nyoman Alit; Ali, Mazurina Mohd (AKRUAL: Jurnal Akuntansi, 2024)
ntroduction/Main Objectives: The research aims to explain how Profitability and ISO 14001 certification impact sustainability reporting. The extent of disclosure in sustainability reporting was influenced by several things, including Profitability and ISO 14001 certificate. It was crucial for mining companies and the primary and chemical sectors that negatively impact the environment and society. Background Problems: Companies were concerned about economic growth, social development, and environmental welfare. Profitability was a measure of company performance, and the ISO 14001 certificate was a reward for implementing the triple bottom line. Activities related to GCG and CSR could be reported separately by the company on the company’s website or in the annual report and sustainability report. Research Methods: This study uses dummy variables for the dependent variable sustainability reporting, so the study used logistic regression analysis. This study uses a sample of mining and elemental and chemical industry companies whose operations significantly impact the environment. Finding/Results: The study results explain that profitability did not affect sustainability reporting because some profitable companies consider it unnecessary to disclose non-financial information. In contrast, companies that experience losses focus on the company’s financial performance. On the other hand, the ISO 14001 certification obtained by the company, which means that the company had carried out environmental management, had a positive impact in that the company discloses sustainability reporting. Conclusion: The ISO 14001 certification had the ability to explain sustainability reporting.